Fluoride and aluminum release from restorative materials using ion chromatography - Zeynep Okte; Sule Bayrak; Ulvi Reha Fidanci; Tevhide Sel (University of São Paulo, 2012)
OBJECTIVE: The aim of this study was to determine the amounts of fluoride and aluminum released from different restorative materials stored in artificial saliva and double-distilled water. Material and METHODS: Cylindrical specimens (10 x 1 mm) were prepared from 4 different restorative materials (Kavitan Plus, Vitremer, Dyract Extra, and Surefil). For each material, 20 specimens were prepared, 10 of which were stored in 5 mL artificial saliva and 10 of which were stored in 5 mL of double-distilled water. Concentrations of fluoride and aluminum in the solutions were measured using ion chromatography. Measurements were taken daily for one week and then weekly for two additional weeks. Data were analyzed using two-way ANOVA and Duncan's multiple range tests (p<0.05). RESULTS: The highest amounts of both fluoride and aluminum were released by the resin-modified glass ionomer cement Vitremer in double-distilled water (p<0.05). All materials released significantly more fluoride in double-distilled water than in artificial saliva (p<0.05). In artificial saliva, none of the materials were observed to release aluminum. CONCLUSION: It was concluded that storage media and method of analysis should be taken into account when the fluoride and aluminum release from dental materials is assessed.